TEACHERâS AND STUDENTSâ TALKS AND THEIR NONVERBAL COMMUNICATION IN THE CLASSROOM INTERACTION - Hafadhotul Husna, Arina; Hartono, Rudi; Sofwan, Ahmad (English Education Journal, 2015)
This study were aimed to find (1) the pattern of teacherâs talks andÂ  studentsâ talks occurred during the classroom interaction, (2) identify teacherâs nonverbal communication and studentsâ nonverbal communication interpreted in their talks. This study was descriptive qualitative method. The participants of this study were one English teacher and 38 students of second semester of Cendekia Utama Nursing College. It used Flanders Interaction Analysis Category System (FIACS), to analyze teacherâs and studentsâ talks and Zoricâs and Smidâs Taxonomy to identify nonverbal communication. The result showed that the most dominant pattern occurred in the classroom interaction at ESP class was the studentsâ participation. The teacher spent (55.7%) while students spent (40.3%) in their time. Teacher produced both direct talks and indirect talks. The amount of direct talks (29.1%) was higher than indirect talks (26.5%). It followed by content cross (34.7%), teacher support (14.3%) and continued by teacher control (6.7%), silence or confusion only spent a little time (4%). The result of nonverbal communication showed that teacher and students used more in oculasics and kinesics. They intentionally made eye contact when they communicated each other and used such facial expression, gesture, body signals, eye movement and head position to support their communications.